(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Strawberry is one of the most important berry crop grown around the world and their consumption increases every year. The introduction of new practices promoting farm sustainability and long-term soil health in strawberry production systems is very essential. Towards environment- and climate-friendly farming practices intercropping can be used to improve soil microbiological activity and biodiversity, and reduce the use of pesticides and mineral fertilizers, while the right choice of intercropped plants is of great importance to achieve these goals. The trials on strawberry intercropping were established in Latvia in 2021. Three treatments with different intercropping plant rotations, including crimson clover, pea, garlic, marigold, and winter rye mix with vetch, were compared to conventional strawberry growing using straw mulch. Trial was installed in three locations: two organic farms and the Institute of Horticulture (LatHort). Thus representing climatically different regions and different soil conditions. Strawberries were grown in 1.2 m distant rows, where in the intercropping treatments, each second interrow was occupied by companion plants. Soil microbial activity was evaluated during vegetation seasons by determining soil respiration rate (SRR) and dehydrogenase activity (DHA) several times per season in 2021 and 2022. Strawberry vegetative development was evaluated at the end of each vegetation season. During the investigation period, soil microbial activity fluctuated during vegetation seasons, depending on growing conditions. In 2021, SRR varied from 1.9 – 3.3 CO2 mg L- 1, while in 2022, from 2.1 - 3.4 CO2 mg L-1. DHA varied from 46 – 134 INTF, µL×????−1 × h in 2021 and 60 – 101 INTF, µL×????−1 × h in 2022. Intercropping had low influence on microbial activity and results differed within each location. Strawberry plant biomass differed among locations and treatments with the highest above-ground biomass observed in LatHort during second growing season in conventional growing system (790 g plant-1).